Maternal feeding style and child weight status among Hispanic families with low-income levels: a longitudinal study of the direction of effects - Sheryl O. Hughes; Thomas G. Power; Teresia M. O'Connor; Jennifer O. Fisher; Nilda E. Micheli; Maria A. Papaioannou (BMC, 2021)
Abstract Background The home environment is a central and modifiable influence on the development of childhood obesity. Evidence supports the central role of parents in shaping problematic child eating behaviors and excess weight. Most studies of feeding emphasize parent-driven influences without taking into account the child's role in eating interactions. Few studies have addressed the bi-directional nature of feeding dynamics in studies of young children. Methods The goals of this study were: 1) to examine if parental feeding styles during preschool (4-5 years) predict child weight status at 7-9 years, and 2) to examine the direction of effects between parental feeding styles and child weight status over time. Participants were part of a larger longitudinal study of Hispanic Head Start families living in the West South Central United States. Data from mother/child dyads were collected at three time points: Time 1 (ages 4-5), Time 2 (ages 5 ½-6 ½), and at Time 3 (ages 7-9). Only data from the Times 1 and 3 were used in the current analyses. A total of 128 mothers and their children had data on all variables needed for the analyses. Assessments included parent-reported feeding styles, feeding practices, acculturation, child eating behaviors, and child height and weight. Hierarchical regression was used to examine the first aim; a cross-lagged panel analysis examined the second aim. Results An indulgent parental feeding style at ages 4-5 was associated with increased child BMI z-score at ages 7-9. Indulgent feeding significantly contributed to child BMI z-score beyond demographics, baseline child BMI z-score, parental acculturation, and child eating behaviors. Regarding the direction of effects in parental feeding interactions, the cross-lagged analyses showed that both indulgent feeding style and authoritative feeding style at Time 1 positively predicted child BMI z-scores at Time 3. Child effects were significant as well. Child BMI z-score at Time 1 positively predicted indulgent feeding and negatively predicted authoritarian feeding at Time 3. Conclusions Indulgent feeding should be addressed in future family-focused childhood obesity initiatives focused on young children and their parents.